2001
DOI: 10.1177/026119290102900509
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Assessment of Cytotoxicity and Carcinogenic Potential of Chemicals: Evaluation of the Cytotoxicity Induced by 58 Metal Compounds in the Balb/3T3 Cell Line

Abstract: A new, mechanistically based, in vitro strategy involving Balb/c 3T3 clone A31-1-1 mouse embryo fibroblasts has been proposed for the determination of the carcinogenic potential of inorganic chemicals, in order to establish priority of metal compounds to be tested and, whenever possible, to compare the in vitro results with the corresponding in vivo data. As a first step in this research, this study reports on the cytotoxic effects of 58 metal compounds in the Balb/3T3 cell line. After harmonisation and standa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 10 publications
1
23
0
Order By: Relevance
“…Recently, in-vitro transformation of SHE cells into a neoplastic state was shown to be associated with overexpression of c-myc and c-Ha-ras oncogenes . The Balb3T3 mouse cell line which has also been a classical model for cell transformation has recently been used for the assessment of cytotoxicity of a large series of metal compounds in order to predict their carcinogenic potential (Mazzotti et al 2001(Mazzotti et al , 2002.…”
Section: Genetic and Cellular Mechanismsmentioning
confidence: 99%
“…Recently, in-vitro transformation of SHE cells into a neoplastic state was shown to be associated with overexpression of c-myc and c-Ha-ras oncogenes . The Balb3T3 mouse cell line which has also been a classical model for cell transformation has recently been used for the assessment of cytotoxicity of a large series of metal compounds in order to predict their carcinogenic potential (Mazzotti et al 2001(Mazzotti et al , 2002.…”
Section: Genetic and Cellular Mechanismsmentioning
confidence: 99%
“…The concentrations of chromium chloride and iron chloride for these studies were chosen on the basis of other reports (Mazzotti et al 2001, 2002) and our earlier investigations. Our previous experiments have shown that both of them slightly stimulated cell proliferation (Terpiłowska and Siwicki 2009, 2010).…”
Section: Disscusionmentioning
confidence: 99%
“…The aim of this study was to examine the effect of chromium(III) and iron(III) used separately and simultaneous treating of chromium(III) and iron(III) on HSV-1 an BVDV replication. The concentrations of chromium chloride and iron chloride for these studies were chosen on the basis of other reports (Mazzotti et al 2001, 2002) and our earlier investigations (Terpiłowska and Siwicki 2009, 2010, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…The procedures for the maintenance and subculture of Balb/3T3 cells were as previously described (10). Whenever possible, metal salts were dissolved in sterile MilliQ water (sometimes at 30°C), at a concentration of 10 -2 M or 10 -3 M. Before incubation with the cells, aliquots of the concentrated metal solutions (stored at 4°C) were added to complete growth medium to give final metal concentrations in the required range of molarity.…”
Section: Cell Culturesmentioning
confidence: 99%
“…The standardised experimental conditions used in this assay were as previously described (10). Cells were plated in 60mm cell culture dishes (FALCON; Cadorago, Como) in 4ml of Dulbecco's modified Eagle's medium (DMEM) low-glucose culture medium containing sodium pyruvate and sodium bicarbonate, without L-glutamine (DME/LOW; EuroClone, CELBIO, Pero, Milano, Italy), supplemented with 10% FCIII serum (200 cells/dish, six dishes per experimental point), and allowed to attach for 24 hours.…”
Section: Cytotoxicity Assaymentioning
confidence: 99%